2019
DOI: 10.1111/pace.13730
|View full text |Cite
|
Sign up to set email alerts
|

Changes in atrial electrophysiological and structural substrate and their relationship to histology in a long‐term chronic canine atrial fibrillation model

Abstract: Background: Atrial fibrillation (AF) is related to numerous electrophysiological changes; however, the extent of structural and electrophysiological remodeling with long-term AF is not well characterized.Methods: Dogs (n = 6) were implanted with a neurostimulator in the right atrium (AF group). No implantation was done in the Control group (n = 3). Electroanatomical mapping was done prior to and following more than 6 months of AF. Magnetic resonance imaging was also done to assess structural remodeling. Animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…To identify the most distinctive and functionally important taxa between PAF and psAF, correlation analyses of taxa and atrial diameter were performed. An enlarged atrium, including left atrial anterior-posterior diameter (LAAPD), left atrial superior-inferior diameter (LASID), left atrial left-right diameter (LALRD), right atrial left-right diameter (RALRD), and right atrial superior-inferior diameter (RASID), is the marker of irreversible atrial remodeling (28)(29)(30)(31). Overall, one family (Holosporaceae), two genera (Methylovulum and Holospora), and five species including Methylovulum miyakonense, Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the most distinctive and functionally important taxa between PAF and psAF, correlation analyses of taxa and atrial diameter were performed. An enlarged atrium, including left atrial anterior-posterior diameter (LAAPD), left atrial superior-inferior diameter (LASID), left atrial left-right diameter (LALRD), right atrial left-right diameter (RALRD), and right atrial superior-inferior diameter (RASID), is the marker of irreversible atrial remodeling (28)(29)(30)(31). Overall, one family (Holosporaceae), two genera (Methylovulum and Holospora), and five species including Methylovulum miyakonense, Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in GM would lead to subsequent changes in choline production. Left atrial enlargement, reflected by atrial diameter, is the marker of irreversible atrial remodeling (28)(29)(30)(31). Also, previous studies have shown that left atrial diameter is an independent risk factor for the development of AF and the long-term outcomes of ablation (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…AF has been identified as a progressive disease, with an “AF begets AF” effect that fosters disease progression (7). Each episode of AF induces atrial electrical and structural remodeling, complex self-sustaining electrical activity, and even irreversible atrial fibrosis, which together contribute to the maintenance of AF (8, 9). Based on an electrocardiogram and AF duration, persistent AF (psAF) is divided into two clinically defined groups: (i) psAF of <12 months (Pers<12m) refers to a duration of AF disease for longer than 7 days but less than 1 year, and (ii) psAF of >12 months (Pers>12m) refers to a duration of AF of greater than 1 year (10).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Areas with reduced bipolar voltage are defined as low-voltage areas (LVAs), and have been reported to correspond to fibrotic regions. 4,5 After pulmonary vein isolation (PVI), LA LVAs have been reported as predictors of recurrent AF. [1][2][3]6 Patients who underwent LVA ablation following PVI demonstrated better long-term outcomes than controls undergoing PVI alone in limited nonrandomized studies.…”
Section: Introductionmentioning
confidence: 99%
“…Left atrial (LA) voltage mapping is performed to identify atrial arrhythmogenic substrates during atrial fibrillation (AF) ablation 1–3 . Areas with reduced bipolar voltage are defined as low‐voltage areas (LVAs), and have been reported to correspond to fibrotic regions 4,5 . After pulmonary vein isolation (PVI), LA LVAs have been reported as predictors of recurrent AF 1–3,6 .…”
Section: Introductionmentioning
confidence: 99%